Design of a high efficiency and low power rectifier circuitry for energy harvester - Ng, Yen Hau (Nanyang Technological University, 2021)
This report presents a topology of a low power and high efficiency multi-stage rectifier circuit for piezoelectric energy harvester. The proposed rectifier comprises of three stages, which are NVC (Negative Voltage Converter) stage, and active diode stage. The rectifier is simulated and implemented in Global Foundries 55nm process using Cadence Virtuoso System Design Platform. Multiple methods to improve the PCE (Power Conversion Efficiency) and VCE (Voltage Conversion Efficiency) are investigated, this report also documented the design process, trade-offs, and comparison between various designs. The results showed the proposed rectifier achieved a 92.43% PCE and 94.11% VCE with 750 load resistance at 1kHz, 2V peak source.